Current Situation and Countermeasures of College Students’ Psychological Cognition of Ideological and Political Theory Course in the New Era - Xiao, Mengqi (Journal of Theory and Practice of Social Science, 2024)
At the Symposium of school ideological and political teachers, it was pointed out that the teaching of Ideological and political theory course cannot be separated from the guidance of teachers. At the same time, we should increase the research on students'cognitive laws and acceptance characteristics, and give full play to students'subjective role. Taking the "the generation after 00s" college students as the research object, this paper explores the current situation of College Students'psychological cognition in the new era [1]. In adjusting the teaching strategy of Ideological and political theory course, teachers formulate the teaching plan of Ideological and political education according to the characteristics of students'psychological cognition, integrate the elements in line with the psychological characteristics of college students in the new era into the teaching classroom, and carry out educational activities in a way more acceptable to students. This is the internal logic of the teaching reform of Ideological and political theory course, It is also an inevitable requirement for college students to grasp the initiative of Ideological and political education and give full play to their subjective role in the new era.